Manajemen Bimbingan Konseling Di SMP Karya Bunda Mandiri Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Hsb, Asmaria; Wijaya, Candra (LP. Ma'arif Janggan Magetan, 2023)
The purpose of this study is to explain how counseling guidance which includes planning, organizing, implementing, and monitoring or evaluating at Karya Bunda Middle School. By using data collection techniques of observation, interviews, and documentation studies. This research is descriptive, data collection is done by reduction, display, and drawing conclusions. Members of the guidance and counseling structure of SMP Karya Bunda were used as research subjects, and supporting subjects for two students and one homeroom teacher were used as subjects for research carried out at SMP Karya Bunda. The findings show that planning begins with the preparation of guidance and counseling service programs, namely in the form of lesson plans, annual, semester, and daily programs. Those providing counseling, advice, and services are prepared before planning begins. All parties, including the school principal, deputy headmaster and homeroom teacher, are involved in organizing guidance and counseling at Karya Bunda Middle School. The coordinator and counseling teacher decide on the formation and implementation of counseling as part of the student organization process. At Karya Bunda Middle School, daily supervision of counseling is carried out by supervising each program implemented and then evaluating it every two weeks to find out how successful the implementation of guidance and counseling services has been.